Evaluasi Administrasi Pembangunan Desa Pesisir Bengkalis Tahun 2024 Melalui Idm dan SDGS Desa: Penelitian - Afriza, Yunika Nuuru; Taryono, Taryono; Siahaan, Mutiara Lasnita (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to evaluate coastal village development in Bengkalis Regency in 2024 using two main instruments: the Village Development Index (IDM) and the Village Sustainable Development Goals (SDGs). The research employed a descriptive-quantitative approach supported by qualitative policy analysis. Data were collected fr om the official publications of the Ministry of Villages (Kemendesa PDTT), the Bengkalis Regency Statistics Agency (BPS), and the Bengkalis Regional Medium-Term Development Plan (RPJMD) 2021–2026. The findings reveal that most coastal villages are categorized as Independent (55%) and Advanced (27%), while 18% remain in Developing and Underdeveloped categories. The SDGs assessment shows the highest achievement in the social dimension (85%), followed by the economic (78%) and environmental (72%) dimensions. These results indicate that coastal village development in Bengkalis has been relatively successful in social and economic aspects but still faces major challenges in the environmental sector, particularly coastal abrasion, mangrove degradation, and waste management. The study highlights that strong IDM performance does not fully guarantee success in environmental sustainability. Therefore, strengthening governance through capacity building of village apparatus, policy integration with RPJMD, and enhancing community participation is essential to achieve inclusive and sustainable coastal village development.